Analisis Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan harga Terhadap Loyalitas Pelanggan Pada Waroeng Spesial Sambal Cabang Gonilan - Sukoharjo Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Pada Mahasiswa Feb Ums) - Marleni, Dina; , Dr. Soepatini, MSi (2016)
This study has the objective to analyze the effect of quality of service (X1), product quality (X2), and price (X3) on customer loyalty (Y) of waroengSpesial SambalGonilan - Sukoharjo with customer satisfaction (Z) as an intervening variable.The population in this study were all active students of the Faculty of Economics and Business UniversitasMuhammadiyah Surakarta, while samples in this study is an active student of the Faculty of Economics and Business, University of Muhammadiyah Surakarta ever made a purchase in a Waroeng Spesial Sambal Gonilan - Sukoharjo.The sampling technique used is convenience sampling by taking 100 respondents in the sample. This study uses a tiered regrsi analysis test / analysis path (Path Analysis). Results of this research is the analysis of regression II F test results of 25.292 and R2 value of 44.1%, whereas in the second regression analysis F test results of 22.532 and R2 value of 48.7%. T test results in the regression analysis I are X1 (3.095); X2 (3,045); X3 (3,484). T test results in the regression analysis II variables X1 and X2 no significant effect, while the results of the t test X3 and Z have significant influence (2,700; 4,793).